2019
DOI: 10.1139/cjas-2017-0166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pig genotype, immunological castration, and use of ractopamine on growth performance, carcass traits, and pork quality for entire male pigs

Abstract: Entire male (EM) pigs (152; ∼30 kg body weight) were used to examine immunocastration using Improvest and feeding ractopamine on growth performance, carcass and meat quality, and fatty acid composition. Timing for administering second dose of Improvest compared dosing at 4 and 8 wk pre-slaughter. A factorial arrangement evaluated two genotypes [Large Whites and Duroc crossbreds (Durocs)] by five management regimens (EM fed control diet, EM fed ractopamine, second dose Improvest 4 wk pre-slaughter, second dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…On the other hand, the pH 24 of the IC originating from the TSL A was even lower than the threshold value for “normal” meat (pH 24 > 5.5), as suggested by Forrest [ 67 ]. Contrary to our results, in studies on crossbreds with 25 or 50% of Pietrain genetics [ 58 , 68 ] and different percentages of Duroc in Large White breed [ 57 ], no interaction between male category and genotype was observed for this trait.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the pH 24 of the IC originating from the TSL A was even lower than the threshold value for “normal” meat (pH 24 > 5.5), as suggested by Forrest [ 67 ]. Contrary to our results, in studies on crossbreds with 25 or 50% of Pietrain genetics [ 58 , 68 ] and different percentages of Duroc in Large White breed [ 57 ], no interaction between male category and genotype was observed for this trait.…”
Section: Resultscontrasting
confidence: 99%
“…There are not many studies dealing with the interaction between the male category and breed on carcass traits [ 3 ]. As to the diverse differential effect of ST in regard to the pig progeny, the existing literature mainly reports no significant or very limited effect [ 57 , 58 , 59 ]. Contrary to the results of the present study, Škrlep et al (2011) [ 43 ] found no interaction in the experiment with two crossbreds (50% Duroc and 50% Pietrain) and three treatments (IM, IC, EM).…”
Section: Resultsmentioning
confidence: 99%
“…The studies with a direct comparison of the male sex category and breed for fat quality traits are, however, scarce and show a limited effect. Park et al [ 42 ], for instance, indicated that the effect of immunocastration on fatty acid composition was relatively consistent in both genotypes (Large White and Duroc crossbreed) evaluated.…”
Section: Fat and Meat Qualitymentioning
confidence: 99%
“…The remaining four chops were individually vacuum sealed and then aged at ≤4 °C for 2 or 7 d and then frozen at −20 °C until further analysis. The frozen chops were thawed over 24 h at <4 °C and used to determine cooking losses and Warner–Bratzler shear force according to the methods of Park et al (2018) .…”
Section: Methodsmentioning
confidence: 99%